Reduction of emesis gravidarum using lavender aromatherapy in the first trimester of pregnancy (literature review) - Idiana, Adri; Dewi, Ratna; Noviyanti, Noviyanti (Science Midwifery, 2024)
Background: Emesis gravidarum is a common condition of nausea and vomiting that occurs during pregnancy, especially in the first trimester. Effective management to reduce these symptoms is important for improving the quality of life of pregnant women. Lavender aromatherapy has been identified as a possible alternative method to reduce emesis gravidarum. The aim of this systematic review was to investigate the existing scientific evidence on the use of lavender aromatherapy in reducing the symptoms of emesis gravidarum in the first trimester of pregnancy. The research method involved a thorough literature search in various sources such as electronic databases, journals, and other related articles. Inclusion criteria were set to select studies relevant to the research topic. The results of the literature search were systematically analyzed and synthesized. The findings of this systematic review showed that the consistent use of lavender aromatherapy resulted in a significant reduction in the symptoms of emesis gravidarum in the first trimester of pregnancy. Several studies reported a decrease in the intensity of nausea and frequency of vomiting after using lavender aromatherapy. However, there was variation in the study designs and sample sizes, which affected the strength of the available evidence. Based on this review, lavender aromatherapy can be a promising choice as an additional therapy to reduce the symptoms of emesis gravidarum in the first trimester of pregnancy.